Evaluating Survival Rate and Growth Performance of Multipurpose Species Raised Under Billion Tree Afforestation Project, Pakistan - Nizar Ali; Anwar Ali; Naveed Ahmad; Ishfaq Ahmad Khan; Habib Ullah (Forestist, 2024)
Afforestation initiatives are increasingly important in addressing global environmental challenges. This study focuses on the Billion Tree Afforestation Project in Pakistan and investigates the survival and growth of multipurpose species planted under the project in the Dera Ismail Khan Forest Division through a stratified random sampling technique. A total of 88 sample plots of 0.1 ha size were taken for 10 plantation sites extended over an area of 461.5 ha. Results showed that the average pit density was 1090 pits/ha, while the regeneration was recorded as 695 individuals/ha. Regarding survival rate, all plantation sites showed the best performance, mostly above 90%. Major species such as Eucalyptus camaldulensis have the highest composition (78%), followed by Acacia nilotica with 14%, while Dalbergia sissoo has the lowest percentage of 7%. The highest growth performance was exhibited by Dalbergia sissoo and Eucalyptus camaldulensis. Dalbergia sissoo attained an average girth of 19 cm and a height of 2.8 m. Eucalyptus camaldulensis attained a mean girth of 16.1 cm and 19.3 cm at 24 months and 27 months, respectively, whereas the mean height at 24 months and 27 months was 2.93 m and 2.8 m, respectively. Furthermore, scatterplots were developed for growth rate analysis between height and girth for all measured individual trees and mean values. The highest correlation was shown by Acacia nilotica with 0.81 and 0.99 coefficient of determination (R2 ) for overall individual values and mean values. The study concluded that the plantation activities in the study area were successful as all the sites showed good survival rates.